THE DEVELOPMENT OF STUDENTS’ VOCABULARY THROUGH EXTENSIVE READING - Sri Fitayanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Sains dan Teknologi Jayapura, 2016)
Now daysit is very important to master English well, extensive reading can be used to improve the basic four skills of the students’. This research aimed to investigate to what extent the students developed their vocabulary through extensive reading. The research was an experimental study. The total of 76 IPS students participanting in the research were devided into two groups. 38 IPS 1 students were treated as the experimental group and another 38 IPS 2 students were treated as the control group. The experimental group was required to do extensive reading, while the control group asked to perform intensive reading. The research data were collected through a pre-test and post-test in vocabulary. The research result revealed that the students treated using the extensive reading technique could significantly improve their vocabulary compared to those students treated using the traditional method or the intensive reading technique. This could be seen as follows: (1) the mean value the students obtained in the pre-test was 75.93 and in the post-test was 89.93; (2) the T-test value of 44.61 was greater than the t-table value of 2.024 (44.61 > 2.024). Besides, the response of the experimental group to the questionaires was positive about the extensive reading method.